New species of the endemic Neotropical caddisfly genus Contulma from the Andes of Ecuador (Trichoptera: Anomalopsychidae) - Holzenthal, RW (2017)
This study was supported by Universidad de Las Américas project AMB.BRT.17.005 “Diversidad y Distribución de Trichoptera de Ecuador” and Minnesota Agricultural Experiment Station projects MIN17-017 and 17-029. Ernesto Rázuri-Gonzales was funded through a doctoral fellowship from Cienciactiva, Consejo Nacional de Ciencia, Tecnología, e Innovación Tecnológica Perú (contract 277-2015- FONCECYT). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.